2011
DOI: 10.1037/a0023340
|View full text |Cite
|
Sign up to set email alerts
|

Is expressive suppression always associated with poorer psychological functioning? A cross-cultural comparison between European Americans and Hong Kong Chinese.

Abstract: The habitual use of expressive suppression as an emotion regulation strategy has been consistently linked to adverse outcomes in a number of domains, including psychological functioning. The present study aimed to uncover whether the suppression-health relationship is dependent on cultural context, given differing cultural norms surrounding the value of suppressing emotional displays. We hypothesized that the negative associations between suppression and psychological functioning seen in European Americans wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
353
12
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 421 publications
(403 citation statements)
references
References 31 publications
31
353
12
7
Order By: Relevance
“…This was in line with a number of recent studies, which indicated that Asian cultures more encourage the suppression of negative emotional expression in comparison with western cultures [1,1821]. This is because the expression of negative emotions may hurt someone else or are detrimental to social and relational harmony, which is valued by interdependent and collectivistic cultural norms in Asia countries [1,20,21]. For example, Friesen [49] observed that Japanese and European participants showed the same facial expressions when watching an emotional film alone, but Japanese showed less negative expressions in the presence of experimenter.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This was in line with a number of recent studies, which indicated that Asian cultures more encourage the suppression of negative emotional expression in comparison with western cultures [1,1821]. This is because the expression of negative emotions may hurt someone else or are detrimental to social and relational harmony, which is valued by interdependent and collectivistic cultural norms in Asia countries [1,20,21]. For example, Friesen [49] observed that Japanese and European participants showed the same facial expressions when watching an emotional film alone, but Japanese showed less negative expressions in the presence of experimenter.…”
Section: Discussionsupporting
confidence: 86%
“…For example, Friesen [49] observed that Japanese and European participants showed the same facial expressions when watching an emotional film alone, but Japanese showed less negative expressions in the presence of experimenter. In addition, many studies reported greater emotion suppression in eastern cultures, such as the report of greater habitual suppression in Asian Americans [37], the report that Asian values discourage assertiveness and encourage self-regulation when interacting with people of higher social status [50], and that suppressing emotion displays was considered as normative in collectivistic nations [21,51]. Consistent with all these evidences, the current study observed that suppression is as effective as reappraisal in dampening experienced negative emotion.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…A comparative study was conducted by, 39 on European American and Chinese students. Results indicated that in European Americans emotion suppression to be associated with adjustment difficulties like poor satisfaction with life and increased level of depression.…”
Section: Psychological Consequences Of Suppressionmentioning
confidence: 99%
“…Despite vast research comparing European Americans with other cultural groups (e.g., Butler et al, 2007;Matsumoto et al, 2008;Soto, Perez, Kim, Lee, & Minnick, 2011;Wei et al, 2013), there is paucity in research comparing value-based cultural differences in emotion suppression in Singapore. The present study aims to address this gap in information.…”
Section: H4mentioning
confidence: 99%